Tindak Kejahatan Korupsi White Collar Crime Model Trend Dan Penyebabnya: Universitas Islam Riau - Muhammad Zulherawan (UIR PRESS, 2019)
The government as a translation of public policy, but in fact spread the oligarchy in power and leaders. At present, regional autonomy is considered the most appropriate solution to the problem of corruption, but it creates new problems, namely the elite and the authorities hijacking the bureaucracy. operands that are always renewable to find loopholes avoid state sanctions.